PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN SATU PINTU DAN TENAGA KERJA KABUPATEN JEMBRANA - Herry Fernandez, I Putu Gede; Supriliyani, Ni Wayan; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2019)
ABSTRACT The Influence of Employee Performance on the Quality of Public Services in One-Stop Integrated Services and Investment Services and Manpower at Jembrana Regency. The purposei ofi writing this scientific paper is to find out whether there is an influence of employee performance oni thei qualityi ofi publici services ini thei One Stop Integrated Services Investment Office and Manpower at Jembrana Regency. While the expected benefits are toi measure employeei performancei against thei qualityi ofi public services in improving service quality. Methoodi usingi in thsi studyi is ai quantitativesi methoodi.Based on descriptive data the assessment of Employee Performance has sgnificants influences on Service Quality.clarified in thati the Employee Performance variable has a strong and positive level of relationsip to the Employee Quality, while the magnitude of the influence of the variable Employee Performance on Service Quality is showed by determinant coefficient value of 0.543. Keywords : Employee Performances, Public Services, DPMPTSPTK